Winter Trees as the Symbol of Female’s Self: Reading Sylvia Plath’s "Winter Trees" through an Eco-feminist Perspective - Gajmer, Sangita (Literary Studies, 2024)
This paper examines the interrelation between poetic experience, expression, womanhood, and creativity with the natural symbol as mentioned in "Winter Trees" by Sylvia Plath. In "Winter Trees,” Plath presents the images or set of winter which itself represents the darkness and pessimism. Plath also seems to compare herself to trees in the winter which stands for her hardships as an emerging female writer in a male-dominating writing tradition. In so doing, the poem reveals a hidden eco-feminist awareness shared by both her biographical as well as ecological symbols related to womanhood and nature. Thus, the poem is an interaction between womanhood and ecological identity.